2005
DOI: 10.1084/jem.20041471
|View full text |Cite
|
Sign up to set email alerts
|

MMTV Env encodes an ITAM responsible for transformation of mammary epithelial cells in three-dimensional culture

Abstract: Expression of immunoreceptor tyrosine-based activation motif (ITAM)-containing signaling proteins is normally restricted to hematopoietic tissues. The basal activity of ITAM-containing proteins is mediated through negative regulation by coreceptors restricted to hematopoietic tissues. We have identified an ITAM signaling domain encoded within the env gene of murine mammary tumor virus (MMTV). Three-dimensional structures derived in vitro from murine cells stably transfected with MMTV env display a depolarized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
123
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(137 citation statements)
references
References 48 publications
(80 reference statements)
9
123
0
Order By: Relevance
“…With respect to their average score, the acinar structure of cells expressing MIGR was very similar to wild-type NMuMG cells (data not shown). MAHB-expressing NMuMG cells developed depolarized acini (Figure 2b), similar to what was seen upon expression of the Env protein of MMTV (Katz et al, 2005). The population of MAHB-expressing acini as a whole were significantly (Po0.0001) more abnormal than those expressing GFP alone ( Figure 2b).…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…With respect to their average score, the acinar structure of cells expressing MIGR was very similar to wild-type NMuMG cells (data not shown). MAHB-expressing NMuMG cells developed depolarized acini (Figure 2b), similar to what was seen upon expression of the Env protein of MMTV (Katz et al, 2005). The population of MAHB-expressing acini as a whole were significantly (Po0.0001) more abnormal than those expressing GFP alone ( Figure 2b).…”
Section: Resultssupporting
confidence: 69%
“…Specifically, we showed that NMuMG cells expressing the viral ITAM-containing protein MMTV Env exhibited several hallmarks of transformation, including depolarized 3D morphology, sensitivity to apoptosis induced by TRAIL or TNFa, and downregulation of E-cadherin and Keratin-18 (Katz et al, 2005). The ability of Env to transform mammary epithelial cells was dependent on an intact ITAM.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…LMP2A and bovine leukemia virus gp 30 were first shown to issue ITAM-dependent signals in T cells (Beaufils et al, 1993). Some functions of the ITAM-containing viral proteins may relate to tumorigenicity, such as survival signalling by activation of the PI3K-Akt pathway by LMP2A and KSHV K1 (Scholle et al, 2000;Swart et al, 2000;Tomlinson and Damania, 2004) and stimulation of cellular migration and invasiveness by LMP2A and MMTV env (Katz et al, 2005;Lu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%